2017
DOI: 10.15405/epsbs.2017.10.62
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Authority And Self-Esteem Among Young Adults

Abstract: Parenting styles play vital role in development of adult self-esteem, and influence of both mother and father is crucial in this regard. Individual and Cultural differences impede the universal consensus on best parenting style for psychological well-being in later life. Collectivist cultures are believed to practice more authority and less flexibility that negatively affect the self-esteem. Current study followed the correlational survey design to investigate the perception regarding father and mother's paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The patient's lack of experience then makes the patient unsure of her abilities, feel unappreciated, and difficult to actualize her abilities. This condition is in line with the results of research conducted by Hayee and Rizvi (2017) that fathers' parenting styles have a significant influence on the development of selfesteem in young adults (Hayee* and Rizvi 2017). The result of the Rosenberg Self-Esteem Scale (RSES) shows a score of 12 which increasingly indicates that the patient has low self-esteem.…”
Section: Resultssupporting
confidence: 86%
“…The patient's lack of experience then makes the patient unsure of her abilities, feel unappreciated, and difficult to actualize her abilities. This condition is in line with the results of research conducted by Hayee and Rizvi (2017) that fathers' parenting styles have a significant influence on the development of selfesteem in young adults (Hayee* and Rizvi 2017). The result of the Rosenberg Self-Esteem Scale (RSES) shows a score of 12 which increasingly indicates that the patient has low self-esteem.…”
Section: Resultssupporting
confidence: 86%
“…The findings suggested that mothers with authoritative parenting style had a correlation with daughters who possessed a negative sense of image for themselves. Therefore, it can be stated that she contributes a vital role in the development of her daughter's self-concept (Hayee & Rizvi, 2017). Moreover, according to attachment theory, a daughter tends to display body ideals that has been either picked by modeling her mother's lifestyle pattern or has been granted approval through her comments to get close to her mother (Bex, 2014).…”
mentioning
confidence: 99%